Monitoring changes in VO2max via the Polar FT40 in female collegiate soccer players - Esco, M. R.; Snarr, R. L.; Williford, H. N. (Journal of Sports Sciences, 2014)
This study was conducted to determine if the Polar FT40 could accurately track changes in maximal oxygen consumption (VO2max) in a group of female soccer players. Predicted VO2max (pVO2max) via the Polar FT40 and observed VO2max (aVO2max) from a maximal exercise test on a treadmill were determined for members of a collegiate soccer team (n = 20) before and following an 8-week endurance training protocol. Predicted (VO2max and aVO2max measures were compared at baseline and within 1 week post-training. Change values (i.e., the difference between pre to post) for each variable were also determined and compared. There was a significant difference in aVO2max (pre = 43.6 ± 2.4 ml/kg·min, post = 46.2 ± 2.4 ml/kg·min, P < 0.001) and pVO2max (pre = 47.3 ± 5.3 ml/kg·min, post = 49.7 ± 6.2 ml/kg·min, P = 0.009) following training. However, predicted values were significantly greater at each time point compared to observed values (P < 0.001 at pre and P = 0.008 at post). Furthermore, there was a weak correlation between the change in aVO2max and the change in pVO2max (r = 0.18, P = 0.45). The Polar FT40 does not appear to be a valid method for predicting changes in individual VO2max following 8 weeks of endurance training in female collegiate soccer players.